EVALUASI DAMPAK PEMEKARAN WILAYAH TERHADAP KESEJAHTERAAN MASYARAKAT DI KOTA TUAL - , Adam Said Rahantan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tual City originally was an integral and inseparable part of the Southeast Maluku regency, with the issue of regional division that developed lately, it resulted the Tual city to be splitted up itself in 2007 to the New Autonomous Region in the province of Maluku. With its characteristics as the island city then the phenomenons such as the disparity area, the span of control and the equitable development remains the major problems perceived by society.This study aimed to: (a) Comparing the regional growth conditions in Tual city before and after regional division